A Narrative of Identification and Apprehension for the Country in the Poetry of Pakistani Female - Sehar, Hadia; Anjum, Naila; Razzaq, Noreen (sourcecoder, 2023)
Urdu poetry adapts with inconstant change of life. Generally literature trends change barely. When special incident happen at large scale a nation or country undergoes with prominent change. These incidents and revolutionary factors enlighten literature and life with new horizons. National identity is a natural demand as well as a source of individuality. It helps in the identification of a nation or human in a social life. From beginning till the current phase of life, national identity is a permanent part of poetry. It has also helped to pave the pathway for human rights as well as the rights of poetess in the society. The national identity and patriotic sentiments of Pakistani women in their poetry have been a recurring theme in their literary works. Through their poetry, they have beautifully encapsulated the spirit of their nation and expressed their love and devotion for their homeland. The important feature of this article is to explore and explicate the role of Pakistani Poetess in national identification and apprehension for the homeland.